2012
DOI: 10.18632/aging.100492
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of DNA repair by NEIL1 and PARP-1: a possible link to aging

Abstract: Oxidative DNA damage accumulates with age and is repaired primarily via the base excision repair (BER) pathway. This process is initiated by DNA glycosylases, which remove damaged bases in a substrate-specific manner. The DNA glycosylases human 8-oxoguanine-DNA glycosylase (OGG1) and NEIL1, a mammalian homolog of Escherichia coli endonuclease VIII, have overlapping yet distinct substrate specificity. Recently, we reported that OGG1 binds to the Poly(ADP-ribose) polymerase 1 (PARP-1), a DNA damage sensor protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 50 publications
7
38
0
Order By: Relevance
“…Similarly, PARP1 binds to the glycosylase NEIL1 which stimulates PARylation activity, whereas activated PARP1 inhibits incision activity of NEIL1. Interestingly, and consistent with the notion of compromised DNA repair during aging, PARP1 binds less efficiently to NEIL1 in old mice compared to young ones [94]. Another, important factor in BER/SSBR is the loading platform X-ray repair complementing factor 1 (XRCC1).…”
Section: Dna Repairsupporting
confidence: 62%
“…Similarly, PARP1 binds to the glycosylase NEIL1 which stimulates PARylation activity, whereas activated PARP1 inhibits incision activity of NEIL1. Interestingly, and consistent with the notion of compromised DNA repair during aging, PARP1 binds less efficiently to NEIL1 in old mice compared to young ones [94]. Another, important factor in BER/SSBR is the loading platform X-ray repair complementing factor 1 (XRCC1).…”
Section: Dna Repairsupporting
confidence: 62%
“…Interaction of hNEIL1 with poly (ADP-ribose) polymerase-1 (PARP-1) [27], a DNA damage sensor, has been observed in vitro and in vivo , and interaction of the C-terminal region of hNEIL1 and the BRCT domain of PARP1 inhibits hNEIL1 incision activity in a concentration-dependent manner. These results suggest that hNEIL1 is not a simple glycosylase/AP-lyase, but plays multiple roles in a highly organized DNA damage control system.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one of the current hypotheses to explain the age-related NAD decline is that this phenomenon could be mediated by accumulation of DNA damage and activation of PARP1 during aging (Figure 4) (Imai and Guarente, 2014). However, depending on the study, it has been observed that levels and activity of PARPs may either decrease or increase during chronological aging or accelerated aging disorders (Bakondi et al, 2011; Braidy et al, 2011; Noren Hooten et al, 2012; Scheibye-Knudsen et al, 2014; Zhang et al, 2014). For example, it was reported that in Cockayne syndrome (CS), an accelerated aging disorder characterized by progressive neurodegeneration, there is aberrant PARP activation leading to decreased SIRT1 activity and mitochondrial dysfunction (Scheibye-Knudsen et al, 2014).…”
Section: What Causes the Nad Decline Observed During The Aging Process?mentioning
confidence: 99%